PENGUATAN KOMUNITAS MELALUI PEMANFAATAN MODAL SOSIAL UNTUK PENANGGULANGAN PENYALAHGUNAAN NARKOBA DI MASYARAKAT - Dwiyantari, MM Sri; Kaligis, Retor AW (Istek Widuri Jakarta, 2015)
Drug abuse in Indonesian society has been very alarming. Currently the national prevalence of drug abusein Indonesia reaches 4 million people or 2% of the total population of Indonesia. This conditions canthreaten the safety of the younger generation, which in turn can disrupt the development of the nation’shuman resource. One of the cases occurred in RT 026 / RW 006 Setu Village, District Setu, SouthTangerang, where a drug user suffered from tuberculosis, immune missing, and eventually died. Basicallythe government has been working hard to tackle the widespread of drugs abuse in society. However, theseefforts will not be effective without the participation of the community. Communities with social capital canbe optimized participation in the community.The assessment results at the community of RT 026 / RW 006 identifies the social capital of the community inthe form of: (1) Residents of participatory; (2) Mutual caring and empathy; (3) The mutual trust; (4) Mutualrespect; (5) adaptive attitude towards the development of science and technology for the togetherness ofresidents; and (6) Uphold the mutual cooperation of citizens. By emphasizing the principle of participation,several programs of action can be done: (1) Drug abuse prevention program for adolescents; (2) The actionprogram for parents; (3) Counseling and affective education for children and adolescents; (4) Theestablishment and development of anti-drug group. Strengthening social capital is expected to be effectiveagainst the drugs abuse in the community and could be developed into a model for action programs in othercommunities. Community leaders and local leaders have a major role in organizing the movement frombelow, with the involvement of professionals in the local community such as community workers,paramedics, midwives, educators, and others.